2021
DOI: 10.1111/micc.12715
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia promoted pulmonary arterial smooth muscle cells proliferation through upregulated calcium‐sensing receptorcanonical transient receptor potential 1/6 pathway

Abstract: Objectives Although both calcium‐sensing receptor (CaSR) and canonical transient receptor potential (TRPC) proteins contribute to chronic hypoxia (CH)‐induced pulmonary arterial smooth muscle cells (PASMCs) proliferation, the relationship between CaSR and TRPC in hypoxic PASMCs proliferation remains poorly understood. The goal of this study was to identify that CH promotes PASMCs proliferation through CaSR‐TRPC pathway. Methods Rat PASMCs were isolated and treated with CH. Cell proliferation was assessed by ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, it should be noted that TRPC channels have previously been shown to be involved in proliferation, migration, apoptosis and pulmonary vascular remodeling in CHPH ( Lin et al, 2004 ; Malczyk et al, 2013 ; Wang et al, 2013 ; Xia et al, 2014 ; Fernandez et al, 2015 ; Smith et al, 2015 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that TRPC channels have previously been shown to be involved in proliferation, migration, apoptosis and pulmonary vascular remodeling in CHPH ( Lin et al, 2004 ; Malczyk et al, 2013 ; Wang et al, 2013 ; Xia et al, 2014 ; Fernandez et al, 2015 ; Smith et al, 2015 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while airway hyperreactivity was decreased, our scRNA‐seq count data for smooth muscle cells were not significantly different in response to CDH in either OVA‐treated or PBS‐treated rats. While no studies have investigated the role of congenital developmental hypoxia on airway smooth muscle, several studies have shown that chronic hypoxia plays a role in airway smooth muscle growth (Lee & Kang, 2019 ; Minamino et al, 2001 ; Xu et al, 2021 ). Although we were interested in assessing the differentially expressed genes and enriched pathways of smooth muscle cells to evaluate gene sets related to growth, there was an insufficient number of cells for robust analysis in our current dataset.…”
Section: Discussionmentioning
confidence: 99%